The French Revolution - Johnson, Douglas W. J (New York : Putnam, 1970)
Recounts the causes and events of the French Revolution with the aid of contemporary illustrations
Includes bibliographical references (p. 125) and index
Keywords: France -- History -- Revolution, 1789-1799 -- Pictorial works